(untitled) (Academicia Globe: Inderscience Research, 2025)
This scientific work analyzes the problems encountered in the development of personal insurance types in Uzbekistan and the ways to overcome them. Although the importance of personal insurance in the country’s insurance market has been increasing in recent years, it has been identified that the legal framework remains insufficiently comprehensive, the level of financial literacy among the population is low, innovative products are not adequately introduced by insurance companies, and there are certain limitations in the quality of services provided. During the study, the structural changes in personal insurance, demographic and socio-economic factors influencing its demand, as well as the impact of market mechanisms were examined. The research substantiates the necessity of strengthening state support mechanisms, diversifying the activities of insurance companies, widely introducing digital technologies, improving insurance culture among the population, and adopting international best practices for the development of personal insurance. The results of the study demonstrate that eliminating these challenges will ensure the stable and effective development of personal insurance in Uzbekistan and enhance the socio-economic protection of the population.